Micromachining using electrochemical discharge phenomenon : fundamentals and applications of spark assisted chemical engraving - Wüthrich, Rolf (Micro & nano technologies, 2009)
This book presents an unconventional and largely unknown technology, which is able to micro-machine at relatively low cost glass, polymers and other materials. This process is called Spark Assisted Chemical Engraving (SACE), or Electro Chemical Discharge Machining (ECDM). First presented in 1968 in Japan by Kurafuji and Suda, this technology was studied essentially in the academic world and mainly applied for micro-fluidic devices. This book explains the fundamentals of SACE, promotes the technology, and encourages researchers and engineers from industry to use it for their specific applications. Therefore, the book, after presenting in details the fundaments of SACE (in particular the Electrochemical Discharges), deals mainly with practical aspects of implementing the machining technology. The book is written so that researchers from fields other than micro-technology (e.g., from life science) will be able to build a simple machining set-up, together with his mechanical work-shop, for individual needs. Topics include: micro- and electrochemical discharge machining (including glass), microfluidics, non-conventional manufacturing, electrochemical discharges, biocompatibility, and anode effects Provides applicable information for engineers in industry dealing with micromachining of glass, polymers, and ceramics Covers a range of microfluidic devices (including micro-TAS) with applications in various fields like chemistry and life sciences.